Innovative techniques and new insights: studying cardiac ionic currents and action potentials in physiologically relevant conditions - Chen-Izu, Ye (2023)
Cardiac arrhythmias are associated with various forms of heart diseases. Ventricular arrhythmias present a significant risk for sudden cardiac death. Atrial fibrillations predispose to blood clots leading to stroke and heart attack. Scientists have been developing patch-clamp technology to study ion channels and action potentials (APs) underlying cardiac excitation and arrhythmias. Beyond the traditional patch-clamp techniques, innovative new techniques were developed for studying complex arrhythmia mechanisms. Here we review the recent development of methods including AP-Clamp, Dynamic Clamp, AP-Clamp Sequential Dissection, and Patch-Clamp-in-Gel. These methods provide powerful tools for researchers to decipher how the dynamic systems in excitation-Ca2+ signaling-contraction feedforward and feedback to control cardiac function and how their dysregulations lead to heart diseases.